2015
DOI: 10.7202/1033406ar
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Impact of the Great Recession on Aboriginal People Living off Reserve in Canada

Abstract: The present analysis seeks to examine whether the 2008 recession had a differential impact on Aboriginal as compared to non-Aboriginal Canadians as measured by the differences in the probability of unemployment between the two groups. Specifically, the present study tests two hypotheses: 1- Aboriginal people have been disproportionately burdened by the Great Recession as compared to non-Aboriginal people, and as a consequence; 2- Aboriginal people are more likely than non-Aboriginal people to be discouraged wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In the years since 2006, the Great Recession of 2008-2009 brought substantial economic instability to many nations, including Canada. A recent study measuring the estimated probabilities of unemployment between Aboriginal and non-Aboriginal groups, for example, found that Aboriginal people were disproportionately burdened by the 2008-2009 downturn (Lamb, 2015). Additionally, issues related to Indigenous peoples have often been at the forefront of recent policy and public discourse.…”
Section: Introductionmentioning
confidence: 99%
“…In the years since 2006, the Great Recession of 2008-2009 brought substantial economic instability to many nations, including Canada. A recent study measuring the estimated probabilities of unemployment between Aboriginal and non-Aboriginal groups, for example, found that Aboriginal people were disproportionately burdened by the 2008-2009 downturn (Lamb, 2015). Additionally, issues related to Indigenous peoples have often been at the forefront of recent policy and public discourse.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these have found that minorities were disproportionately impacted. The only study in this area, Lamb (2015), including Native Americans finds that Aboriginal people in Canada have been disproportionately burdened.…”
Section: Introductionmentioning
confidence: 99%
“…23 Indigenous people were disproportionately burdened by the 2008 economic crisis: the probability of unemployment was higher and more persistent for them than for non-Indigenous people. 24 11% of employed First Nations people living on reserve were self-employed in 2017, with employed men more likely to be self-employed (13%) than women (8%). 52…”
Section: Employment and Unemployment Ratesmentioning
confidence: 99%